2013
DOI: 10.1021/jf402107t
|View full text |Cite
|
Sign up to set email alerts
|

Summer Deficit-Irrigation Strategies in a Hedgerow Olive cv. Arbequina Orchard: Effect on Oil Quality

Abstract: Different irrigation treatments were applied to a superintensive orchard of 'Arbequina' olives ( Olea europaea L.) during three seasons (2007-2009) to examine the effect of the amount of water and the moment of irrigation in summer on the virgin olive oil (VOO) quality. A control was made (CON) with irrigation to maintain the root zone close to field capacity; two water deficit treatments were employed with irrigation at 30% of CON, either from the end of fruit drop to the end of July (DI-J) or from the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 36 publications
6
36
0
1
Order By: Relevance
“…Moisture levels below 50 and about 60% are difficult for the mill to extract the oil (California Olive Ranch, personal communication). Other researchers have also found that too high a fruit moisture content decreases oil extraction Gómez-del-Campo, 2013;Ramos and Santos, 2009). …”
Section: Oil Yieldsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moisture levels below 50 and about 60% are difficult for the mill to extract the oil (California Olive Ranch, personal communication). Other researchers have also found that too high a fruit moisture content decreases oil extraction Gómez-del-Campo, 2013;Ramos and Santos, 2009). …”
Section: Oil Yieldsmentioning
confidence: 97%
“…Trees in SHD orchards require topping and pruning to maintain a suitable tree size to allow over-the-row machines to harvest the fruit. Finally, Gómez-del-Campo (2013) found that applying 30% of soil water field capacity from fruit drop to the end July resulted in 16% water savings with no loss in oil yields.…”
Section: Introductionmentioning
confidence: 99%
“…Full irrigation (FI) decreased the concentration of total phenol and o -diphenol in VOOs, with wide differences in the concentration of the aglycone derivate of oleuropein. In olive trees of cultivar ‘Arbequina’ subjected to four irrigation management approaches, at different stages of fruit development, the highest content of total phenols, hydroxytyrosol acetate, 3,4-DHPEA-EDA, p -HPEA-EDA, 3,4-DHPEA-EA, o -diphenols, tyrosyl elenolate ( p -HPEA-EA), and total secoiridoids was detected in trees stressed from the end of fruit drop to the end of July (Del Campo and García, 2013). Fruit ripening and irrigation treatments have been also found to induce considerable variation in the concentrations of secoiridoid derivatives of hydroxytyrosol and tyrosol in VOO of cultivars ‘Cornicabra’ (Gümez-Rico et al, 2006), ‘Souri’ (Dag et al, 2008), and ‘Cipressino’ (Martinelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If less water is available, farmers should look toward increasing water productivity (production per unit of total water applied) through the optimization of irrigation management (Fereres and Evans, 2006; Iniesta et al, 2009; Fereres et al, 2014). For olive orchards, the regulated deficit irrigation (RDI) (Tognetti et al, 2005, 2007; Iniesta et al, 2009; Gómez del Campo and García, 2013) is the most commonly used irrigation strategy and consists of imposing water stress during phenological phases that are relatively insensitive to water deficit. Goldhamer (1999) reported that the pit hardening phase is the least sensitive to water deficit, and recommended the adoption of RDI, restricting irrigation during this phase.…”
Section: Introductionmentioning
confidence: 99%